Complete mitochondrial genome of a stonefly, Nemoura papilla (Plecoptera: Nemouridae) - Jinjun Cao; Ying Wang; Gaoyan Ma; Weihai Li (Mitochondrial DNA. Part B. Resources, 2019)
The complete sequence of the mitochondrial DNA of Nemoura papilla, has been completed and annotated in this study. The circular genome is 15,774 bp in length with an A + T content of 68.0% and contains 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), 2 ribosomal RNA genes (rRNAs), and a putative control region. All tRNA genes have the typical cloverleaf structure, with an exception for tRNASer(AGN). All PCGs use normal start codon ATN, while ND1 use TTG as the start codon. Meanwhile, 11 PCGs use the typical termination codons TAN, except COII and ND5, which stopped with the incomplete termination signal T. Phylogenetic analysis suggests that N. papilla is closely related to N. nankinensis. Nemouridae + Capniidae was assigned to be the sister of Taeniopterygidae.